Empowering climate resilience in Matara: anticipatory action and the AWARE Platform - Alahacoon, Niranga; Amarasinghe, H.; Indrasena, R.; Gunasundara, W.; Kaushalya, C.; Nethmi, K.; De Silva, R.; Amarnath, Giriraj (International Water Management Institute, 2025)
The two-day training program “Empowering Climate Resilience in Matara: Anticipatory Action and the AWARE Platform” brought together government officials, university academics, technical agencies, and community leaders to strengthen local capacity for proactive disaster preparedness in Matara—one of Sri Lanka’s most flood-prone districts. Due to increasing climate extremes and recurrent flooding in Matara, the program emphasized the need to shift from reactive disaster response toward anticipatory, evidence-based action. Participants were introduced to core concepts of Disaster Risk Reduction (DRR), Anticipatory Action (AA), impact-based forecasting, and trigger development. A key highlight was the hands-on training on the AWARE Platform, IWMI’s digital decision-support tool that integrates climate and hydrological forecasts, early warning systems, early action protocols, and early financing mechanisms. Through practical demonstrations, group exercises, and simulations, trainees learned how to translate scientific data into localized early actions and sector-specific protocols for agriculture, livestock, health, education, and water, sanitation, and hygiene (WASH). The program fostered collaborative learning, enabling academia, government institutions, and humanitarian partners to jointly design anticipatory strategies tailored to Matara’s flood risks. Participants emphasized the need to institutionalize AA within district systems and integrate these concepts into university curricula. The training strengthened technical capacity, enhanced coordination, and advanced the vision of a resilient Matara equipped to act before disasters strike.